Challenges and Solutions in Implementing a Healthy Indonesia Program with a Family Approach - Mujiati; Eva Sulistiowati; Andy Leny Susyanty; Tetra Fajarwati; Aprildah Nur Sapardin; Made Dewi Susilawati; Rossa Avrina; Siti Nur Hasanah; Nova Sri Hartati; Agus Dwi Harso; Tince Jovina; Makassari Dewi; Andre Yunianto (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The Healthy Indonesia Program with a Family Approach (PISPK) is conducted bypuskesmas by integrating existing resources, with the family’s target. All familieswill get access to comprehensive health services. The implementation of PISPKsince 2016 has not been optimal because it has many obstacles. The analysis aimsto identify the obstacles, and to find solutions to implemented PISPK optimally.Implementation research was carried out using Participatory Action Research(PAR). The team (researcher and subject) implemented PISPK together based onstages that integrated into puskesmas management, at 4 puskesmas in SouthLampung. Researchers assisted and recorded data collected qualitatively (self-assessment, in-depth interviews, Focus Group Discussion), and quantitatively.There are any obstacles occurred in the implementation of PISPK such as theabsence of regulations and cross-sectoral supports; lack of knowledge andsupport from village officials, community leaders, and the public; limitedresources; lack of understanding of the substantive; application; lack of dataanalysis capabilities. These obstac-les can be minimized by making somebreakthroughs, such as advocacy and issuance of local government regulations onPISPK involving cross-sectors; increase socialization; periodic coordination,monitoring, and evaluation; making innovations (On Job Training, collaborationwith universities and health volunteer, Healthy Family Coverage Pocket Book,developing data analysis methods). The implementation of PISPK has manyobstacles that can be minimized by optimizing existing potentials and supportfrom stakeholders. Puskesmas need to increase socialization; team organizing;data analysis; coordination, and routine monitoring evaluation. Pusdatin needs toimprove KS applications to be more user-friendly.